How is cultural diversity positioned in teacher professional standards? an international analysis. Issue 3 (26th May 2016) - Santoro, Ninetta; Kennedy, Aileen
ABSTRACT: Unprecedented levels of global mobility mean that culturally homogenous classrooms are now increasingly rare. This brings with it challenges for teachers and raises issues about what constitutes quality teaching and teachers. Professional standards are commonly seen as a key policy instrument through which teacher quality can be enhanced. This article presents an analysis of teacher professional standards from five of the most culturally diverse nations in the English-speaking world. Using critical discourse analysis, we examine how culturally and linguistically diverse learners and culturally responsive pedagogy are positioned, and what the standards stipulate teachers should know, and be able to do, in fulfilling their professional obligations. We conclude by raising concerns about how the official representations of teaching in particular national contexts fail to position culturally diverse learners and culturally responsive teaching as a priority.